WTO Provision and Higher Education in Nepal - Koirala, Amit (International Journal of Social Sciences and Management, 2014)
The World Trade Organization (WTO) agreements cover a wide range of activities such as agriculture, textiles and clothing, banking, telecommunications, government purchases, industrial standards and product safety, food and sanitation regulations and intellectual property. Under the WTO agreements, countries cannot normally discriminate between their trading partners. Imported and locally produced goods should be treated equally. The same should apply to foreign and domestic services, and to trademarks, copyrights and patents. Education has been considered as one of the trades in the WTO. It has been argued that the accession of membership to WTO will be very helpful in the development of a country like Nepal so, this paper especially tries to find out the dilemmas and prospective on higher education in Nepal with respect to WTO provision. DOI: http://dx.doi.org/10.3126/ijssm.v1i4.10965 Int. J. Soc. Sci. Manage. Vol-1, issue-4: 139-142